FAMILY HISTORY OF PREMATURE CORONARY ARTERY DISEASE AS AN INDEPENDENT PREDICTOR OF DISEASE SEVERITY: AN OBSERVATIONAL SINGLE-CENTRE STUDY - Dr. Muhammad Musa; Dr. Farhat Ullah Khan; Dr. Naeem Khan; Dr. Muhammad Idrees Khan; Dr. Ayesha Bibi; Dr. Rahim Dil Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Coronary artery disease (CAD) is still a critical and prevalent global health concern, and early onset further increases the threat. It has been established that the history of premature CAD depends on family significantly and is an independent risk factor that determines the development and course of the disease.Objective: To determine whether a family history of premature CAD is an independent predictor of angiographic disease severity in patients diagnosed with CAD at a tertiary care hospital in Pakistan.Materials and Method: This cross-sectional study conducted at multi centers including Department of Cardiology, Ayub Teaching Hospital Abbottabad and Hayatabad Medical Complex Peshawar from June 2023 to June 2024. A total of 320 patients being referred for coronary angiography were evaluated in terms of disease severity using the Gensini score. Data were analyzed using SPSS v26.Results: Individuals with a positive family history had higher Gensini scores (74.2 ± 18.6) and triple-vessel disease rates (39.4%) than those without (21.9%, 58.9 ± 16.3; p